Performance Pay, CEO Dismissal, and the Dual Role of Takeovers - Burkart, Mike; Raff, Konrad (Review of Finance, 2015)
Abstract We propose that an active takeover market provides incentives by offering acquisition opportunities to successful managers. This allows firms to reduce performance-based compensation and can rationalize loss-making acquisitions. When choosing its acquisition policy and the quality of its board, each firm ignores the adverse effect on other firms’ acquisition opportunities and takeover threat. As a result, the takeover market is not sufficiently liquid and too few takeovers occur. Furthermore, liquidity in the takeover and managerial labor markets are inversely related. When poaching managers becomes more profitable, firms invest more in board quality which in turn reduces the incidence of takeovers.